(untitled) (Jurnal Bahasa, 2003)
Literary study in its teaching-learning involved some aspects such as the students, literatures software and hardware, teachers approach and methods. Selection of literary books, teaching-learnings design and programme must conform with the relative heterogenity of the students and times to achieve the critical literary appreciation. The programmes of literary education and teaching must be selected on the basic of literary structure with its basic humanistic themes.forms, and modes of expression eagerly romantic, realistic, comic, tragic, and ironic with due to the dimensions of teaching-learning: humanistic development, humanistic tradition, and form.